Public debt and economic growth in sub-Saharan Africa: Nonlinearity and threshold effects - Princewill U. Okwoche; Christine S. Makanza (Cogent Economics & Finance, 2023)
Most studies on the effects of debt on growth, particularly following the global financial crisis, have focused mainly on the advanced and emerging countries. Our focus on sub-Saharan Africa (SSA) derives from the recent experience of slow growth at a time of rising debt in the sub-region. This approach allows us the opportunity to fit a model that accounts for some region-specific characteristics, such as the quality of institutions and policies, conflict, and adverse terms of trade shocks. Our dataset comprises 24 SSA countries spanning 39 years from 1980 to 2018. We employ a variety of panel estimation techniques suitable for addressing the problems of endogeneity and cross-section dependence. The fixed effects instrumental variable technique is used as the baseline technique, while the bias corrected least-squares dummy variable and the limited information maximum likelihood are used for robustness. In agreement with recent literature, we find compelling evidence in support of a nonlinear relationship between debt and growth, which suggests that public debt may become harmful to growth if it rises beyond a certain level. Further to that, the evidence presents a threshold estimate of 78-85% in most cases. Some variations in threshold estimates based on differences in empirical estimation techniques were observed, which point to the need to localize debt-growth studies to country-specific cases for more applicable results. Policy implications based on these findings are discussed.
Keywords: E62; H63; 330; Growth; nonlinearity; cross-section dependence; endogeneity; gross government debt